A recent survey on image watermarking using scaling factor techniques for copyright protection - Ernawan, Ferda; Ariatmanto, Dhani (Springer, 2023)
This survey presented a discussion of the existing scaling factor and adaptive scaling factor in image watermarking schemes. The discussion included several issues: robustness, imperceptibility and computational time for embedding a watermark. This survey also discussed the general concept of the image watermarking, transform method, embedding region and security on the existing watermarking scheme. This paper also discussed the recent use of watermarking techniques, potential issues and available solutions in adaptive watermarking schemes. Furthermore, the performance summary of the state-of-art embedding techniques is presented and analysed for future research. This literature review became useful to researchers to know the current challenges in embedding a watermark image. This survey information can be used to design an efficient embedding watermark for copyright protection.